Early Childhood Teachers' Beliefs on the Contribution of Instructional pictures in Developing Young Children’s Linguistic Skills - AlAli, Rommel Mahmoud; Al-Barakat, Ali Ahmad (Journal of Ecohumanism, 2024)
This study investigates early childhood teachers' beliefs regarding the contribution of instructional pictures in developing young children’s linguistic skills. A carefully designed questionnaire assessed teachers' beliefs on how instructional pictures, such as pictures and drawings, contribute to language development. The questionnaire's validity and reliability were confirmed through expert evaluation and a test-retest method, respectively. It was distributed to 570 randomly selected participants in northern Jordan. The findings revealed that many early childhood teachers have positive beliefs about instructional pictures, viewing them primarily as tools for enhancing linguistic meaning, developing children's language skills, and fostering positive attitudes towards language learning. More specifically, the study showed that teachers believe instructional pictures are effective in improving children's pronunciation accuracy, promoting concrete thinking, increasing enjoyment and enthusiasm for language learning, enriching vocabulary, and enhancing reflective thinking in expressing ideas. These findings illustrate how instructional pictures support improving children's attention, developing their oral and written skills, and facilitating multisensory approaches to language learning. Interestingly, the analysis indicated that teachers' academic qualifications did not significantly influence their beliefs about the contribution of instructional pictures in language learning environments. Given these findings, it is crucial to integrate additional resources such as digital visual materials and educational apps that support the use of instructional pictures to enhance language skills.